Corporate governance and its implications for sustainability reporting quality in Latin American business groups (2020)
ABSTRACT: This paper aims to study the factors determining the quality of sustainability reporting in Latin American business groups. Applying a logistic regression model, this study is pioneer in establishing how some distinct corporate variables of business groups influence disclosure quality of Corporate Social Responsibility practices in these groups in emerging economies. The results show that control concentration in the groups negatively affects the quality of sustainability reporting. Variables such as foreign ownership, the age of the business group and board size help business groups to improve the quality of their sustainability and voluntary disclosure practices. These results form the basis to conduct further studies on voluntary disclosure in business groups, since they evidence that corporate governance has implications for the group’s sustainability and their voluntary disclosure, especially in the institutional context of developing economies where sustainability is an emerging topic in its link with the nature of the firm (business group).